Decoding ferroptosis: transforming orthopedic disease management - Huo, Guanlin; Lin, Yumeng; Liu, Lusheng; He, Yuqi; Qu, Yi; Liu, Yang; Zhu, Renhe; Wang, Bo; Gong, Qing; Han, Zhongyu; Yin, Hongbing (Frontiers in Pharmacology, 2024)
As a mechanism of cell death, ferroptosis has gained popularity since 2012. The process is distinguished by iron toxicity and phospholipid accumulation, in contrast to autophagy, apoptosis, and other cell death mechanisms. It is implicated in the advancement of multiple diseases across the body. Researchers currently know that osteosarcoma, osteoporosis, and other orthopedic disorders are caused by NRF2, GPX4, and other ferroptosis star proteins. The effective relief of osteoarthritis symptoms from deterioration has been confirmed by clinical treatment with multiple ferroptosis inhibitors. At the same time, it should be reminded that the mechanisms involved in ferroptosis that regulate orthopedic diseases are not currently understood. In this manuscript, we present the discovery process of ferroptosis, the mechanisms involved in ferroptosis, and the role of ferroptosis in a variety of orthopedic diseases. We expect that this manuscript can provide a new perspective on clinical diagnosis and treatment of related diseases.